Re-imagining Tatian: The Damaging Effects of Polemical Rhetoric - Koltun-Fromm, Naomi (Journal of early Christian studies, 2008)
Tatian, a second-century Christian apologist, is best known on the one hand for his much admired and only extant text, the Oratio ad Graecos, and on the other for heresy. Starting with Irenaeus, Tatian develops a reputation particularly among the western Fathers for heresy and extreme asceticism—including sexual renunciation, vegetarianism, and abstention from alcohol. In the late fourth century Tatian reappears as the reputed (and heretical) author of the Diatessaron, possibly the gospel harmony most popular in the Syriac-speaking churches. In medieval Syriac Christian writings, due to a conflation of these two earlier associations, Tatian's reputation transforms itself yet again. Thus, due to his presumed now generic-heretical standing, these authors further accuse Tatian of removing the NT genealogies from his harmonized text thus undermining the human element in christological theory. Yet I think it can be demonstrated that these two reputations—the one of heretical encratism, and the other of heretical Christology—in fact reflect polemical constructions created to deflect external anti-Christian polemic and internal cross-Christian conflict onto another group rather than historical reality.